Before eminent domain : toward a history of expropriation of land for the common good - Reynolds, Susan, 1929- (Studies in legal history., 2010)
In this concise history of expropriation of land for the common good in Europe and North America from medieval times to 1800, Reynolds contextualizes the history of an important legal doctrine regarding the relationship between government and the institution of private property.